China's urban unemployment challenge - Wei Ge (Transformation, Integration and Globalization Economic Research (TIGER), 2008)
Since the launching of its economic reform and opening up programs in 1979, China has experienced an unprecedented economic expansion, as its real GDP growing at an annual average rate of about 10%. Despite the robust performance, the pressure for employment creation has continued to persist and the situation of excess supply of labor, especially in the urban area, has been worsening. This paper explores the changing patterns of the urban labor market, and identifies the main characteristics of the urban unemployment. On that basis, some viable policy responses will be highlighted.
Keywords: J21; J6; O18; O53; R23; 330; Labor; Unemployment; Urban; Transition; China; Asia; Städtischer Arbeitsmarkt; Städtischer Arbeitsmarkt; China